Um filho para a Pátria: a construção da memória em torno do general Tibúrcio e a escrita da história do Ceará (1887-1937) - Rodrigues, Karla Cristine (2016)
Entitled "A son to the country: the construction of memory around General Tiburcio (1887-1937)", this research aims to understand the "memory work" involved in the election and promotion of this called hero of Ceará - which has developed in specific time and space. We understand that the way they elect these heroes lets see their own perspective of thinking and writing history, therefore, to look at the past. General Tibúrcio certainly was not the first or the last called hero for Ceará, however, the actions of certain groups - Ceará Historical Institute, press, Ceará Museum, militares poblications - we were noted the intention to make it a hero from Ceará who represented Ceará (part) in front (all) the country Brazil. The proposed cut is between 1887-1937, the empire ends and beginning of the Republic in Brazil, at which time the Republic was taking its first steps and sought to consolidate and legitimize. Ceará intended to have a hero who figured in the history of Brazil. We can say that his figure was promoted shortly after his death, when, in 1887, the square in the center of the city gets its name. In 1888, the monument is inagurated in the center of the square, and this whole process reported in the press, especially the newspaper "Liberator" in "Column Monument Tiburcio," written by the newspaper during 1887 and 1888. When the centenary of his birth was approaching, 1937, it took place in the magazines of Ceará Historical and Geographical Instituite, and the Historic Museum of Ceará, in 1934 and 1935, with the acquisition of "Biographical objects" and ordered paint by the director, Eusébio de Sousa. And finally, with the birth centenary commemoration with the celebration of achievement in Praca General Tiburcio and organization of a biography whose title was: General Tiburcio: Great Soldier and Thinker. This biography was organized by Eusébio de Sousa (Director of the Museum and the State Public Archives.) The sources used in the research are, in summary: Squares; Monuments; Newspapers, Biographies; Journal of Ceará Historical Institute and the collection of Ceará Museum.